Results of research on backlash compensation in a power electric drive by low-power electronic device - Semen L. Samsonovich; Boris K. Fedotov; Nikolay B. Rozhnin; Roman V. Goryunov (Acta Polytechnica, 2022)
This article considers the feasibility of restoring and maintaining the kinematic accuracy of the support-rotary device drives by introducing a backlash compensation device into the control system. The power electromechanical drives of support-rotary device considered in this article contain two motors, the summation of the torques of which is carried out on a common output shaft. It is shown that the restoration of the required kinematic accuracy of the drives can be achieved by introducing one of two variants of an electronic device for backlash compensation into the control system. In the first variant, equal and opposite displacement signals are introduced into the control signals of the motors. The second variant introduces an electronic cross-connections backlash compensation scheme was into the control system. The study of the operation of the support-rotary device drive system with two backlash compensation devices carried out by a simulation method showed that the use of a cross-connection scheme is the most preferable and effective. As a result of the research, it was shown that the introduction of an electronic backlash compensation device into the control system makes it possible to ensure the operability of the power electromechanical drives of a support-rotary device with initial kinematic accuracy.